(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
This study aims at exploring Chinese college students’ reticence in English classes. It is focused on finding the reasons why the students choose to keep silence in the classes and revealing the relationship between their reticence and identity construction. The study has been carried out with narrative inquiry and narrative grammar analysis has been applied to the interview data. It is found that major reasons for the participants’ reticence in English classes include the transfer of perception of incompetence, a habit of being silent in classes and personality from the learner’s past self to the present self, the learner’s lack of investment in study and the insufficient assistance from the teachers. Based on the findings, it is concluded that through the reticence in classes, the students are constructing an identity of an inactive student and it is the students and the teachers that are the ‘heroes’ in the narrative who can make efforts to retrieve the value of active participation in classes to improve the students’ learning achievements.